Gut Microbiota Markers in Obese Adolescent and Adult Patients: Age-Dependent Differential Patterns - Del Chierico, Federica; Abbatini, Francesca; Russo, Alessandra; Quagliariello, Andrea; Reddel, Sofia; Capoccia, Danila; Caccamo, Romina; Ginanni Corradini, Stefano; Nobili, Valerio; De Peppo, Francesco; Dallapiccola, Bruno; Leonetti, Frida; et al. (Frontiers in Microbiology, 2018)
Obesity levels, especially in children, have dramatically increased over the last few decades. Recently, several studies highlighted the involvement of gut microbiota in the pathophysiology of obesity. We investigated the composition of gut microbiota in obese adolescents and adults compared to age-matched normal weight (NW) volunteers in order to assemble age- and obesity-related microbiota profiles. The composition of gut microbiota was analysed by 16S rRNA-based metagenomics. Ecological representations of microbial communities were computed, and univariate, multivariate and correlation analyses performed on bacterial profiles. The prediction of metagenome functional content from 16S rRNA gene surveys was carried out. Ecological analyses revealed a dissimilarity among the subgroups, and resultant microbiota profiles differed between obese adolescents and adults. Using statistical analyses, we assigned, as microbial markers, Faecalibacterium prausnitzii and Actinomyces to the microbiota of obese adolescents, and Parabacteroides, Rikenellaceae, Bacteroides caccae, Barnesiellaceae, and Oscillospira to the microbiota of NW adolescents. The predicted metabolic profiles resulted different in adolescent groups. Particularly, biosynthesis of primary bile acid and steroid acids, metabolism of fructose, mannose, galactose, butanoate and pentose phosphate and glycolysis/gluconeogenesis were for the majority associated to obese, while biosynthesis and metabolism of glycan, biosynthesis of secondary bile acid, metabolism of steroid hormone and lipoic acid were associated to NW adolescents. Our study revealed unique features of gut microbiota in terms of ecological patterns, microbial composition and metabolism in obese patients. The assignment of novel obesity bacterial markers may open avenues for the development of patient-tailored treatments dependent on age-related microbiota profiles.